DEVELOPMENT OF A DIGITAL SIMULATION- BASED INTERACTIVE MODULE FOR JUNIOR HIGH SCHOOL STUDENTS ON MECHANICS IN THE NATIONAL SCIENCE OLYMPIAD (OSN) - Nining Kusumastuti; Fiki Taufik Akbar (Joint Prosiding IPS dan Seminar Nasional Fisika, 2026)
This study introduces a breakthrough by providing the first interactive digital simulation-based module specifically designed for OSN physics training at the junior high school level, integrating multiple simulation platforms into a unified and innovative learning resource, which has not been found in previous OSN modules. The module was developed using the Research and Development (R&D) method, following the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). It was designed as a web-based resource using Canva and integrated with simulations from GeoGebra and PhET to present physics concepts dynamically and interactively. Validation by three experts from the Institut Teknologi Bandung resulted in an average score of 3.0 for content validity and 3.2 for media validity (on a scale of 4.0), both categorized as very valid. The module was then tested on ten junior high school students from Serang Regency who were prospective OSN participants. The training showed moderate effectiveness, with an average N-gain score of 0.38. Feedback from the participants and a supervising teacher yielded practicality scores of 3.5 and 3.8 (on a scale of 4.0), respectively, indicating the module is highly practical. Based on these results, the module is considered effective, valid, and highly practical, making it suitable as a supporting tool for OSN science training at the junior high school level.